(untitled) (Research, Society and Development, 2023)
Objective: To assess the effect of social and maternal health characteristics on the prevalence of cesarean delivery. Methods: Population-based study with pregnant women aged 18 years or older, registered and monitored by the public health service, in the urban area. Demographic, socioeconomic, health history, and obstetric characteristics were collected using previously tested and standardized questionnaires. Prevalence Ratios (PR) were calculated in the bivariate analysis and odds ratios (OR) adjusted by logistic regression according to a hierarchical model. Results: The prevalence of cesarean sections was 63.74%. After adjustments, age greater than or equal to 35 years (OR = 2.15; 95%CI 1.22 - 3.79), having a partner (OR = 1.56; 95%CI 1.02 - 2. 37), overweight/obesity (OR = 1.57; 95%CI 1.13 – 2.17) having prenatal care (OR = 1.65; 95%CI 1.17 – 2.32) and presenting different characteristics in the pregnancy, such as breech or transverse fetal presentation and type of multiple pregnancy (OR = 3.98; 95%CI 1.54 – 10.31). Conclusion: It was found that the prevalence of cesarean section is above acceptable levels and that clinical factors and social determinants are associated with this practice. Thus, greater political attention to social and health conditions during pregnancy and childbirth is necessary.